Automatización de un sistema de riego para el control de humedad en los cultivos del invernadero #2 del Centro Experimental Salache en la Universidad Técnica de Cotopaxi. - Pardo Solano, Franklin Vladimir (2020)
The present research project was carried out in the sector of Salache Province of Cotopaxi with the objetive of designing and implementing an automated system for the control of moisture inside a greenhouse. This allowed us to control the variable dependent on moisture that varies according to the type of crop. The automation of the system was carried out through the information that was collected through the moisture sensors located in the different sections of the crops, which recorded the moisture in the soil and proceeded to determine whether it is in the range set for the subsequent opening or closing of the solenoid valves. And at the same time the ignition of centrifugal pumps. The system consists of four solenoid valves distributed in the different sections. Two pumps of 1 Hp that will work to reach the necessary pressure, the pumps carried out the process of drip irrigation that allowed to reduce the use of water. For the selection of the automatic or manual mode, a machine human interface was incorporated too for easy user handling. The implementation of the automated system for moisture control improved the efficiency of the irrigation system, it met the main objective of the 40 PSI (pressure required for irrigation of greenhouse crops), allowed us to save the resource "Water" in 50 %. And it could be a beneficial project for students and the agricultural sector because they will be able to improve their skills in this area. With the implementation of the automated irrigation system for moisture control it was possible to find that the pressure necessary to be able to perform the misting process arrives because this pressure is 40 Psi and with the system exceeds that pressure reaching about 60 Psi.